Preparation method of photoelectric semiconductor material NaBiS2

By performing high-temperature smelting reaction in vacuum sealed quartz tubes, the molar ratio of Na2S and Bi2S3 was optimized, and the high-quality and stable NaBiS2 materials were successfully prepared, which solved various problems in material preparation in the prior art and achieved large-scale Possibility of scale production.

CN119433714APending Publication Date: 2025-02-14HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411482659.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing NaBiS2 material synthesis methods have problems such as poor crystallinity, high impurity content, high equipment cost and complex process, making it difficult to achieve large-scale production and high stability material preparation.

Method used

By optimizing the molar ratio of raw material Na2S powder and Bi2S3 powder, using a molar ratio of 1.00 to 1.10:1.00, the high-temperature smelting reaction between Na2S and Bi2S3 is carried out in a vacuum sealed quartz tube and under the protection of carbon tubes, and successfully produced a high-temperature smelting reaction with NaBiS2 material with photoelectric characteristics.

Benefits of technology

It realizes high-quality and stable synthesis of NaBiS2 materials. The product has high crystallinity and high purity, is simple to operate, low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433714A_ABST
    Figure CN119433714A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of photoelectric materials, and discloses a preparation method of a photoelectric semiconductor material NaBiS2, which comprises the following steps: weighing raw material Na2S powder and raw material Bi2S3 powder according to a molar ratio of (1.00-1.10): 1.00, fully mixing, putting into a carbon tube, putting into a quartz tube together, vacuumizing, and sealing; and the obtained vacuum sealed quartz tube is subjected to heat preservation at 800-900 DEG C for 10-12 hours for high-temperature smelting, and a NaBiS2 material smelting cast ingot can be obtained. According to the preparation method, the proportion of the raw materials Na2S powder and Bi2S3 powder is optimized, and the Na2S and Bi2S3 are subjected to high-temperature smelting reaction in the vacuum sealed quartz tube under the protection of the carbon tube, so that the semiconductor material NaBiS2 with the photoelectric characteristic is successfully prepared. The solid-phase reaction is achieved through high-temperature smelting, the target NaBiS2 material is obtained, preparation is convenient and fast, and large-scale preparation can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optoelectronic materials, and more specifically, relates to a method for preparing a photoelectric semiconductor material NaBiS2. Background Art

[0002] Optoelectronic semiconductor materials play a vital role in the field of energy conversion and storage, especially in applications such as photovoltaics and photodetectors. Although traditional optoelectronic materials, such as silicon, indium gallium arsenide (InGaAs), and perovskite materials have achieved certain success in practical applications, they still have some shortcomings. For example, the preparation process of silicon-based materials is complicated and costly, perovskite materials face challenges in long-term stability and environmental adaptability, and indium gallium arsenide materials are limited by the scarcity and high cost of raw materials.

[0003] In recent years, sodium bismuth sulfur (NaBiS2) has attracted attention as a new type of optoelectronic semiconductor material. Compared with other optoelectronic materials, NaBiS2 has the following significant advantages: 1) NaBiS2 is composed of sodium, bismuth and sulfur elements, which are abundant, low-cost, and non-toxic to the environment. 2) NaBiS2 has a direct band gap of nearly 1.4eV, which is very suitable for photovoltaic applications. It can effectively absorb the visible light part of the solar spectrum and achieve a high photoelectric conversion efficiency. 3) NaBiS2 has a high light absorption coefficient and can absorb a large number of photons in a thinner material layer, reducing the requirements for material thickness. 4) NaBiS2 exhibits good chemical stability under air and humidity conditions, which can overcome the problem of decomposition of some perovskite materials under environmental conditions.

[0004] As known in the prior art, the crystal structure of NaBiS2 material is a face-centered cubic structure, and the unit cell parameters are The space group is The three elements Na, Bi and S are contained in an atomic ratio of 1:1:2. Na and Bi occupy the cation positions randomly and compete with each other, as shown below. Figure 1 shown.

[0005] At present, the synthesis methods of NaBiS2 materials mainly include solution method, chemical vapor deposition (CVD) and solid phase reaction method. However, these methods still face some challenges in actual production. For example, NaBiS2 prepared by solution method has poor crystallinity and high impurity content, which can easily lead to unstable performance of optoelectronic devices; although the CVD method can prepare high-quality thin films, the equipment cost is high and the process is complicated, which is not suitable for large-scale production; and the traditional solid phase reaction method, due to the volatility of sodium and sulfur elements, often finds it difficult to achieve stable products. Therefore, if an environmentally friendly and easy-to-operate method can be explored to synthesize NaBiS2, it will be of great significance for the research and development of NaBiS2. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing a photoelectric semiconductor material NaBiS2, wherein the ratio of raw material Na2S powder and Bi2S3 powder is optimized, a molar ratio of 1.00 to 1.10:1.00 is adopted, and Na2S and Bi2S3 are subjected to high-temperature melting reaction in a vacuum-sealed quartz tube and under the protection of a carbon tube, and a semiconductor material NaBiS2 with photoelectric properties is successfully prepared. The present invention utilizes high-temperature melting to achieve a solid-phase reaction to obtain the target NaBiS2 material, which is easy to prepare and can be prepared on a large scale.

[0007] To achieve the above object, the present invention provides a method for preparing a photoelectric semiconductor material NaBiS2, which is characterized by comprising the following steps:

[0008] (1) weighing raw material Na2S powder and raw material Bi2S3 powder in a molar ratio of 1.00-1.10:1.00 under a protective atmosphere;

[0009] (2) fully mixing the raw material powder obtained in step (1), and placing the obtained mixed powder in the carbon tube;

[0010] (3) Place the carbon tube containing the mixed powder in step (2) in a quartz tube and evacuate the tube to a pressure not exceeding 10 -5 Sealing after support;

[0011] (4) The vacuum-sealed quartz tube obtained in step (3) is kept at 800°C-900°C for 10-12 hours for high-temperature smelting to obtain a NaBiS2 material smelting ingot.

[0012] As a further preferred embodiment of the present invention, in step (1), the molar ratio of the raw material Na2S powder to the raw material Bi2S3 powder is 1.05:1.00.

[0013] As a further preferred embodiment of the present invention, the preparation method further comprises the steps of:

[0014] (5) The smelted ingot obtained in step (4) is crushed into powder to obtain NaBiS2 material powder.

[0015] As a further preferred embodiment of the present invention, in step (4), the temperature is kept at 800° C.-900° C. for 10-12 hours for high temperature smelting, and the heating time used is 6-10 hours;

[0016] After the high temperature smelting is completed, the temperature is lowered to room temperature, and the cooling time used is 24-36 hours.

[0017] As a further preferred embodiment of the present invention, in step (4), the high temperature smelting is preferably carried out at a temperature of 900° C. for 10-12 hours.

[0018] As a further preference of the present invention, in step (1), the protective atmosphere is nitrogen.

[0019] As a further preferred embodiment of the present invention, in step (5), the pulverizing is firstly pulverized using an agate grinding body and then pulverized into powder using a planetary ball mill.

[0020] Through the above technical scheme conceived by the present invention, compared with the prior art, by optimizing the ratio of raw material Na2S powder and Bi2S3 powder, using a molar ratio of 1.00-1.10:1.00, in a vacuum sealed quartz tube, under the protection of a carbon tube, Na2S and Bi2S3 are subjected to a high temperature smelting reaction, and a semiconductor material NaBiS2 with photoelectric properties is successfully prepared. The method for synthesizing NaBiS2 of the present invention adopts a high temperature smelting method, which is simple to operate, short in time, low in cost, and large-scale mass production.

[0021] Due to the volatility of sodium and sulfur, the target NaBiS2 material is often not obtained by the traditional solid phase reaction method. The present invention is based on the smelting method. By controlling the molar ratio of the raw material Na2S powder and Bi2S3 powder to 1.00-1.10:1.00, applying a vacuum-sealed reaction environment, and controlling the smelting temperature and time to be kept at 800℃-900℃ for 10-12 hours, these technical obstacles are successfully overcome, and the stable synthesis of high-quality NaBiS2 is achieved. The product obtained by smelting does not need annealing treatment, and can be cooled after the smelting is completed (natural cooling or temperature-controlled cooling with further extended cooling time can be used). The method of the present invention not only solves the defects of the traditional method, but also lays a foundation for the large-scale production of NaBiS2.

[0022] The NaBiS2 synthesized by the high-temperature smelting method of the present invention is highly crystallized and has excellent stability. In particular, the molar ratio of the raw material Na2S powder and Bi2S3 powder can be preferably controlled to 1.05:1.00. In a vacuum-sealed quartz tube and under the protection of a carbon tube, the Na2S and Bi2S3 undergo a high-temperature smelting reaction to obtain a NaBiS2 product with good crystallinity and high purity.

[0023] The preparation method of the present invention successfully obtains NaBiS2 material, which is an n-type semiconductor material with a face-centered cubic crystal structure. The prepared NaBiS2 can be used in new photovoltaic devices such as solar cells and photodetectors.

[0024] The present invention adopts a high-temperature smelting method to synthesize NaBiS2, which is simpler to operate, takes less time, has low equipment requirements and is suitable for large-scale production, and has the characteristics of being environmentally friendly and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the crystal structure of the optoelectronic semiconductor material NaBiS2.

[0026] Figure 2 This is the X-ray diffraction pattern of the ingot powder of the optoelectronic semiconductor material NaBiS2 synthesized in Examples 1 to 4.

[0027] Figure 3 The differential scanning calorimeter analysis results of the ingot powder of the optoelectronic semiconductor material NaBiS2 prepared in Example 3.

[0028] Figure 4 This is the X-ray diffraction pattern of the ingot powder of the optoelectronic semiconductor material NaBiS2 synthesized in Example 5.

[0029] Figure 5 This is the X-ray diffraction pattern of the ingot powder of the optoelectronic semiconductor material NaBiS2 synthesized in Example 6. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Example 1

[0032] A method for synthesizing NaBiS2 based on high temperature smelting comprises the following steps:

[0033] (1) Prepare raw material powder: weigh Na2S and Bi2S3 in a molar ratio of 1.00:1.00 under a protective atmosphere (the protective atmosphere used in this embodiment is specifically nitrogen; of course, other inert atmospheres such as Ar gas can also be used as protective atmospheres), specifically weigh 0.5267g of Na2S and 3.4705g of Bi2S3. The error range of the weighing balance used in this embodiment is ±0.0005g.

[0034] (2) Powder mixing: The initially weighed powders were manually mixed in a mortar for 10 minutes, and the mixed powders were placed in the carbon tubes;

[0035] (3) Vacuum sealing: Place the carbon tube containing the mixed powder in a quartz tube and evacuate it to a pressure no greater than 10 -5 Sealing after support;

[0036] (4) High-temperature smelting: The vacuum-sealed quartz tube is placed in a box furnace for high-temperature smelting. The smelting conditions are: slowly heating from room temperature to 900°C over 10 hours, keeping at 900°C for 12 hours, and then slowly cooling to room temperature over 36 hours to obtain a molten ingot.

[0037] (5) Ingot crushing: The ingot obtained by high-temperature smelting is first crushed using an agate mortar and then crushed into powder using a planetary ball mill. The crushing using the agate mortar is specifically performed by manual grinding for 30 minutes, and the grinding time using the planetary ball mill is 6 hours.

[0038] Example 2

[0039] The only difference between this embodiment and embodiment 1 is that step (1) is to weigh Na2S and Bi2S3 in a molar ratio of 1.03:1.00 (i.e., 0.5425 g of Na2S and 3.4705 g of Bi2S3). The other steps and specific parameter conditions are the same as those in embodiment 1.

[0040] Example 3

[0041] The only difference between this embodiment and embodiment 1 is that step (1) is to weigh Na2S and Bi2S3 in a molar ratio of 1.05:1.00 (i.e., 0.5531 g of Na2S and 3.4705 g of Bi2S3). The other steps and specific parameter conditions are the same as those in embodiment 1.

[0042] Example 4

[0043] The only difference between this embodiment and embodiment 1 is that step (1) is to weigh Na2S and Bi2S3 in a molar ratio of 1.10:1.00 (i.e., 0.5794 g of Na2S and 3.4705 g of Bi2S3). The other steps and specific parameter conditions are the same as those in embodiment 1.

[0044] Example 5

[0045] The only difference between this embodiment and embodiment 2 is that the temperature program used in step (4) high temperature smelting is changed to: slowly heating from room temperature to 800°C over 10 hours, keeping at 800°C for 12 hours, and then slowly cooling to room temperature over 36 hours to obtain a smelted ingot. The other steps and specific parameter conditions are the same as those in embodiment 2.

[0046] Example 6

[0047] The only difference between this embodiment and embodiment 3 is that the temperature program used in step (4) high temperature smelting is changed to: slowly heating from room temperature to 900°C over 10 hours, keeping at 900°C for 10 hours, and then slowly cooling to room temperature over 36 hours to obtain a smelted ingot. The other steps and specific parameter conditions are the same as those in embodiment 3.

[0048] Figure 2 The X-ray diffraction diagram of the NaBiS2 ingot powder prepared in Examples 1 to 4, the legend "NaBiS2 (1:1)" in the figure corresponds to the NaBiS2 ingot powder prepared in Example 1, the legend "NaBiS2 (1.03:1)" in the figure corresponds to the NaBiS2 ingot powder prepared in Example 2, the legend "NaBiS2 (1.05:1)" in the figure corresponds to the NaBiS2 ingot powder prepared in Example 3, and the legend "NaBiS2 (1.1:1)" in the figure corresponds to the NaBiS2 ingot powder prepared in Example 4. Figure 2 As shown, the diffraction peaks of NaBiS2 (PDF#01-078-0148) were detected in each sample prepared in Examples 1 to 4.

[0049] Further, from Figure 2 It can be seen that the raw materials Na2S and Bi2S3 can be mixed in different proportions according to the molar ratio of 1.00 to 1.10:1.00, and the NaBiS2 product can be synthesized by high temperature smelting method. The figure shows that the diffraction peak of the NaBiS2 ingot powder prepared in Example 3 is sharp and has good crystallinity, and it is most consistent with the diffraction peak of PDF#01-078-0148. No other impurity peaks are observed in the figure, which confirms that the synthesized NaBiS2 ingot powder has high purity. The NaBiS2 ingot powder synthesized in Example 1, Example 2 and Example 4 contain other impurity peaks, indicating that the purity of the obtained products is not as good as the NaBiS2 ingot powder obtained in Example 3.

[0050] Figure 3 The differential scanning calorimeter analysis result of the NaBiS2 ingot powder prepared in Example 3 shows that the NaBiS2 ingot powder undergoes thermal decomposition at 271.897°C, indicating that the NaBiS2 ingot powder has good stability at room temperature.

[0051] Figure 4 The X-ray diffraction pattern of the NaBiS2 (1.03:1) ingot powder prepared in Example 5 is shown in FIG. Figure 4 It can be seen that when the reaction temperature is lowered to 800°C, NaBiS2 products can be synthesized. The figure shows that the diffraction peaks of the NaBiS2 ingot powder prepared in Example 5 are sharp and have good crystallinity. Of course, a small amount of other impurity peaks are also observed.

[0052] Figure 5 The X-ray diffraction pattern of the NaBiS2 (1.05:1) ingot powder prepared in Example 6 is shown in FIG. Figure 5 It can be seen that when the reaction time is reduced to 10 hours, NaBiS2 products can be synthesized. The figure shows that the diffraction peak of the NaBiS2 ingot powder prepared in Example 6 is sharp and has good crystallinity, and no other impurity peaks are observed, which confirms that the synthesized NaBiS2 ingot powder has high purity.

[0053] Comparative Example 1

[0054] A method for synthesizing NaBiS2 based on high temperature smelting comprises the following steps:

[0055] (1) Prepare raw material powder: weigh Na2S and Bi2S3 in a molar ratio of 1.00:1.00 under a protective atmosphere (wherein the protective atmosphere is specifically nitrogen), specifically weighing 0.5267 g of Na2S and 3.4705 g of Bi2S3. The error range of the weighing balance used in this embodiment is ±0.0005 g.

[0056] (2) Powder mixing: The initially weighed powders were fully mixed manually in a mortar for 10 minutes, and the obtained mixed powders were placed in the carbon tubes.

[0057] (3) Vacuum sealing: Place the carbon tube containing the mixed powder in a quartz tube and evacuate it to a pressure no greater than 10 -5 Sealed after support.

[0058] (4) High-temperature smelting: The vacuum-sealed quartz tube is placed in a box furnace for high-temperature smelting. The smelting conditions are: slowly heating from room temperature to 800°C over 10 hours, keeping at 800°C for 6 hours, and then slowly cooling to room temperature over 24 hours to obtain a molten ingot.

[0059] (5) Ingot crushing: The ingot obtained by high-temperature smelting is first crushed using an agate grinder.

[0060] Compared with Example 1, the ingot obtained in Comparative Example 1 did not react completely, and some unreacted NaS2 and Bi2S3 were still present.

[0061] Comparative Example 2

[0062] A method for synthesizing NaBiS2 based on high temperature smelting comprises the following steps:

[0063] (1) Prepare raw material powder: weigh Na2S and Bi2S3 in a molar ratio of 1.00:1.00 under a protective atmosphere (wherein the protective atmosphere is specifically nitrogen), specifically weighing 0.5267 g of Na2S and 3.4705 g of Bi2S3. The error range of the weighing balance used in this embodiment is ±0.0005 g.

[0064] (2) Powder mixing: The initially weighed powders were fully mixed manually in a mortar for 10 minutes, and the mixed powders were directly placed in a quartz tube.

[0065] (3) Vacuum sealing: The quartz tube containing the mixed powder is evacuated to a pressure not exceeding 10 -5 Sealed after support.

[0066] (4) High-temperature smelting: Place a vacuum-sealed quartz tube in a box furnace for high-temperature smelting. The smelting conditions are: slowly raise the temperature from room temperature to 900°C over 10 hours, keep it at 900°C for 10 hours, and then slowly cool it down to room temperature over 36 hours to obtain a smelted ingot.

[0067] Compared with Example 1, in this comparative example, since no carbon tube was used for protection, the volatile substances Na and S corroded the quartz tube, causing the quartz tube to burst during the smelting process, so that the reactants were in direct contact with the air, and the obtained ingot contained other impurities.

[0068] The above embodiments are only examples. For example, the protective atmosphere may be other inert gases, such as Ar gas, in addition to N2. For another example, after smelting, in addition to temperature-controlled cooling and extended cooling time, natural cooling and furnace cooling may also be used.

[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a photoelectric semiconductor material NaBiS2, characterized in that: The following steps are involved: (1) weighing raw material Na2S powder and raw material Bi2S3 powder in a molar ratio of 1.00-1.10:1.00 under a protective atmosphere; (2) fully mixing the raw material powder obtained in step (1), and placing the obtained mixed powder in the carbon tube; (3) Place the carbon tube containing the mixed powder in step (2) in a quartz tube and evacuate the tube to a pressure not exceeding 10 -5 Sealing after support; (4) The vacuum-sealed quartz tube obtained in step (3) is kept at 800°C-900°C for 10-12 hours for high-temperature smelting to obtain a NaBiS2 material smelting ingot.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the raw material Na2S powder to the raw material Bi2S3 powder is 1.05:1.

00.

3. The preparation method according to claim 1, characterized in that: The preparation method further comprises the steps of: (5) The smelted ingot obtained in step (4) is crushed into powder to obtain NaBiS2 material powder.

4. The preparation method according to claim 1, characterized in that: In step (4), the temperature is kept at 800°C-900°C for 10-12 hours for high temperature smelting, and the heating time used is 6-10 hours; After the high temperature smelting is completed, the temperature is lowered to room temperature, and the cooling time used is 24-36 hours.

5. The preparation method according to claim 1, characterized in that: In step (4), the high temperature smelting is preferably carried out at a temperature of 900° C. for 10-12 hours.

6. The preparation method according to claim 1, characterized in that: In step (1), the protective atmosphere is nitrogen.

7. The preparation method according to claim 3, characterized in that: In step (5), the pulverization is specifically performed by first using an agate grinding body to pulverize, and then using a planetary ball mill to pulverize into powder.